Poplave spreminjajo lastnosti prsti in s tem možnosti njihove rabe - Vovk, Ana (Geografija v šoli, 2024)
This study investigates soil properties in the flood-prone area of the Dravinja Valley, Slovenia, which covers Slovenske Konjice, Slovenska Bistrica, Poljčane, Makole, and Majšperk. The Dravinja River floods due to its high flows and elevated groundwater levels, which leads to stagnant surface water, particularly in lower elevations, even well away from the immediate riverbed. The study aimed to characterise these floodplain soils and assess how their properties are affected by prolonged waterlogging. Soil samples were collected from 11 sites using a soil auger. Ten main physical and chemical properties were measured and analysed for their correlation with flooding events. The results contribute to a broader understanding of floodplain soil characteristics and their response to flooding. The findings can inform future soil management strategies in floodprone areas and promote the provision of essential soil ecosystem services.
Keywords: Dravinja (reka); Dravinja river; Dravinja Valley; Dravinjska dolina; floods; lastnosti prsti; poplave; prst (pedologija); reke; soil; soil properties; water